Microplastic pollution in the Belawan Estuary, Indonesia: Evidence from aquatic biota and polymer characterization - AHMAD MUHTADI; RUSDI LEIDONALD; NUR MAIYAH; MOHD YUSOFF ISHAK; RIZAL MUKRA (Society for Indonesian Biodiversity, 2025)
Abstract. Rangkuiti AM, Leidonald R, Maiyah N, Ishak MY. 2025. Microplastic pollution in the Belawan Estuary, Indonesia: Evidence from aquatic biota and polymer characterization. Biodiversitas 26: 2002-2010. Microplastic pollution causes widespread contamination of coastal and marine environments. Although microplastic pollution has been studied in marine and estuarine environments across Indonesia, studies in North Sumatra are lacking. This study assessed microplastics (Mps) contamination of aquatic organisms in the Belawan Estuary. Aquatic biota was captured using ambai fishing gear, and the intestines were dissected for analysis. After degrading the organic material using an alkaline digestion method, microplastic particles were identified based on their shape, size, and quantity. Four types were identified: fibers, films, fragments, and pellets. Pellet microplastics were the most abundant, with an average of 24.21 particles per gram in fish and an average of 13.62 particles per gram in crustaceans, followed by fibers, fragments, and films. The size of the microplastic particles ranged from 27 to 1940 ?m. The abundance of MPs was higher in fish (average: 63.899 particles per g) than in crustaceans (average: 30.97 particles per gram). Carnivorous fish species were most contaminated with microplastics, including Epinephelus areolatus, Plotosus lineatus, and Neotrygon kuhlii, all of which are demersal. Fourier-transform infrared spectroscopy identified six polymers: polypropylene, polystyrene, polyethylene, polyvinyl chloride, polyethylene terephthalate, and polyamide. This study highlights severe microplastic contamination in the Belawan Estuary and underscores the need for urgent action to address this environmental threat.